The Synergy of Digital Literacy and Communicative Competence in English Language Education (Journal of Science-Innovative Research in Uzbekistan, 2025)
This study examines the relationship between digital literacy and communicative competence in English among 25 Uzbek undergraduate EFL learners, using a correlational research design. Digital literacy, including the ability to use digital tools for communication and information processing, was evaluated through practical tasks and self-assessment surveys. Communicative competence was assessed through role-play, group discussions, and writing tasks. The results revealed a strong and statistically significant positive correlation (r=0.957r = 0.957r=0.957, p